2013
DOI: 10.1007/s00299-013-1548-5
|View full text |Cite
|
Sign up to set email alerts
|

The Gossypium hirsutum WRKY gene GhWRKY39-1 promotes pathogen infection defense responses and mediates salt stress tolerance in transgenic Nicotiana benthamiana

Abstract: WRKY transcription factor genes play significant roles in the response to biotic and abiotic stresses. Cotton (Gossypium hirsutum) is an important fiber and oil crop worldwide. We isolated and characterized GhWRKY39-1, which is a group IId WRKY gene that is present as a single copy in the cotton genome. Quantitative PCR analyses indicated that GhWRKY39-1 was induced by pathogen infection, defense-related signaling molecules, and abiotic stresses, such as NaCl and methyl viologen. An analysis of the subcellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 47 publications
2
60
0
Order By: Relevance
“…The activity level was significantly higher than non-transgenic varieties, but the activity change rates of PAL, PPO and POD in the transgenic line was not significantly higher than in the untransformed variety which indicated that transformed hrpZpsta gene soybean had the ability to respond quickly to pathogen infection. This is consistent with reports of other plants on enzyme activity (Shi et al, 2014;Lei et al, 2010).…”
Section: Resultssupporting
confidence: 93%
“…The activity level was significantly higher than non-transgenic varieties, but the activity change rates of PAL, PPO and POD in the transgenic line was not significantly higher than in the untransformed variety which indicated that transformed hrpZpsta gene soybean had the ability to respond quickly to pathogen infection. This is consistent with reports of other plants on enzyme activity (Shi et al, 2014;Lei et al, 2010).…”
Section: Resultssupporting
confidence: 93%
“…SlWRKY39 expression was significantly up regulated in both BABA-treated and P. indica-colonized plants in response to pathogen attack suggesting the role of BABA and P. indica in modulating both SA-and MeJA-dependent defence pathways. Recently it is reported that constitutive overexpression of GhWRKY39-1 in Nicotiana benthamiana conferred a greater resistance to infection by both the bacterial pathogen Ralstonia solanacearum and the fungal pathogen Rhizoctonia solani through SAdependent/MeJA-dependent defence pathways [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that overexpression of stress responsive genes in plant may improve its adaption to various stresses and increase the yield (Li et al, 2014; Shi et al, 2014). Previously, JIOsPR10 was reported to be involved in the biotic stress tolerance, such as M. oryzae infections (Kim et al, 2004).…”
Section: Discussionmentioning
confidence: 99%